Pharmaceutical Mini-Tablets Overview - Mohammad F. Bayan1 , Hala M. Sbaih1 and Mohamed J. Saadh2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Oral dosage forms are considered as the most preferred dosage forms to various age groups of patients.However, conventional solid dosage forms (tablets and capsules) have been associated with some issues;such fluctuation in the plasma drug concentration and swallowing difficulty for some patients. This advocatesthe need for the continuous development and improvement of tablets and capsule to enhance therapeuticefficacy and increase patient acceptance. Mini tablets technology has been developed to minimize theseproblems. It aims to facilitate oral administration with minimal swallowing difficulty (especially inpediatrics and geriatrics) and deliver a therapeutic agent, selectively and effectively, to be targeted in acertain position in the body. The most benefit of this technique is the ease of production with facilitatedcontrol of stability problems. The size and shape uniformity, with smooth surface area, make minitabletsattractive to be incorporated with different medications for the efficient treatment of chronic diseases. Thisoverview outlines properties, production requirements, formulation options and evaluation methods of minitablets.